2021
DOI: 10.1093/bjsw/bcab013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Bibliographic Database Searching for Literature Reviews: Case Study on Child Protection Decision-Making

Abstract: Skills of the ‘information age’ need to be applied to social work. Conceptual and practical aspects of using online bibliographic databases to identify research were explored using multi-professional decision-making in child protection as a case study. Five databases (Social Science Citation Index, Scopus, Medline, Social Work Abstracts and Cochrane Central Register of Controlled Trials) were searched for relevant studies, retrieving 6,934 records of which fifty-eight studies were identified as relevant. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…PubMed, which is renowned for its extensive coverage of the biomedical literature, is crucial for health-related systematic reviews. The use of these databases ensures a thorough search process, as highlighted in the work of Alfandaria and Taylor (56) , who found that replicability varied from platform to platform.…”
Section: Discussionmentioning
confidence: 99%
“…PubMed, which is renowned for its extensive coverage of the biomedical literature, is crucial for health-related systematic reviews. The use of these databases ensures a thorough search process, as highlighted in the work of Alfandaria and Taylor (56) , who found that replicability varied from platform to platform.…”
Section: Discussionmentioning
confidence: 99%
“…Principally, questions about the effectiveness of distinct interventions or services are at the heart of rigorous systematic reviews incorporating statistical meta-analysis of experimental results, such as those taken within the Cochrane Collaboration and Campbell Collaboration (Higgins et al, 2020; Kugley et al, 2017). The methodology used here has more general applicability and may also accommodate questions about views and experiences of those receiving or providing services, as well as prevalence and correlates of social problems (Alfandari & Taylor, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The research topic was converted into four distinct concept groups:<decision making> AND <multiprofessional> AND <child protection> AND <children and youth>. Then, search terms for each concept were combined into the initial search formula, with index terms assigned according to the facilities of the database (for the detailed search formula, see Alfandari & Taylor, 2021).…”
Section: Hospital-based Contextmentioning
confidence: 99%
See 2 more Smart Citations